Pelatihan Kesehatan Gigi dan Mulut pada Siswa Sekolah Dasar - Aisyah AR; Suciyati Sundu; Dewi Sartika; Fidzah Nurfajrina Murad; Faradillah Usman (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
Oral and dental health training for elementary school students is an important preventive effort to build the habit of maintaining oral and dental hygiene from an early age. This program aims to increase students' knowledge about the importance of dental and oral care and train them in the correct tooth brushing technique. This activity begins with counseling on dental health problems that children often face, such as cavities due to bad habits and high sugar consumption. Furthermore, students are given practical training on how to brush their teeth effectively. The results of the training showed that students were very enthusiastic and were able to understand and practice the correct tooth brushing technique. Question and answer sessions and direct practice strengthened their understanding, while giving prizes increased students' motivation to apply the knowledge they had gained. This training is expected to be the first step in forming a generation that is aware of the importance of oral and dental health.